PRODUCTION SYSTEMS AND INCOME GENERATION FROM THE BLIGON GOAT FARMING IN THE RURAL COMMUNITY IN GUNUNGKIDUL OF YOGYAKARTA PROVINCE, INDONESIA - Widiati, Rini (2016)
This study was conducted to Investigate the potentials of Bligon Goat Farming System for income generation in the rural community of Girimulyo Village, Gunungkidul Regency of Yogyakarta Province.Data was collected from 30 Bligon goat farmers which taken purposively as the respondents with semi structural interview. Enterprise budgeting of Bligon goat farming business made to analyze profitability and feasibility that could be used for further planning for farmers to develop their business. The result of this study showed that the Bligon goat farming was a potential alternative to be developed for income generation that can be developed in rural communities to generate of income. Nevertheless, government policy was urgently needed such as provide loans with low interest rate below 6%. Furthermore, the production system in the term of kidding interval and mortality in the breeding system were needed to be improved. kidding interval should be lower than 8 months and mortality of kid until 12 months age should be lower than 6% would give higher farm income value. It was a challenge for scientists to develop technology that supports the improvement in those two aspects.